Ghosts of the past: the uncanny presence of Nazi sources in post-war sociolinguistics. (2nd September 2022) - Hutton, Christopher
ABSTRACT: This paper considers the at-first-sight puzzling presence of Nazi linguistics as sources in two post-war sociolinguistic works, authored by Joshua Fishman and Uriel Weinreich respectively. It offers an account of who these Nazi linguists were and the basic ideological positions they represented. The argument is made that the presence of these sources reflects a wider problem in post-war sociolinguistics, namely a lack of awareness of the nature of interwar language politics. The question of Umvolkung ('assimilation', 'transethnization', 'ethnoconversion') in interwar Europe concerned state boundaries and the status of ethnolinguistic minorities. In the post-war United States, assimilation was understood in the context of indigenous and migrant languages and cultures, within a language ecology dominated by English. Post-War US identity politics concerned social and institutional space, rather than the ownership and occupation of territory. The same concept may be potentially toxic in one sociopolitical context and progressive in another.